Webinar Edukasi dalam Rangka Percepatan Cakupan Vaksinasi COVID-19 di Kota Ambon - Nazliah Awwaliah R. Syarbin; Christiana Rialine Titaley; Fadhila Nuralifa Fairus; Yudhie Djuhastidar Tando; Bertha Jean Que; Yuniasih Mulyani Jubeline Taihuttu; Ony Wibriyono Angkejaya; Indrawanti Kushadiani; Irwan Irwan; Amanda Gracia Manuputty; Maimuna Latuconsina; Delsony Gerson Leunupun (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
The rates of cases and deaths from COVID-19 started to decline following the increased coverage of vaccination. In Indonesia, the coverage of COVID-19 vaccination has not met the national target, including in Ambon City. By conducting a webinar, this activity aimed at improving the knowledge of the development and the importance of the COVID-19 vaccination program amongst the academic community of Pattimura University and health workers at Dr. M Haulussy Hospital, the main COVID-19 referral hospital in Ambon City.This webinar was conducted by the Faculty of Medicine of Pattimura University (FK UNPATTI) on 10 December 2021 as part of the efforts to accelerate the COVID-19 vaccination coverage in Ambon. There were 275 participants (including students, lecturers and health workers from Dr. M. Haulussy Hospital, the main referral hospital in Ambon City) filled out the evaluation questionnaires (pre- and post-test). Resource persons were from the Health Office of Ambon City, FK UNPATTI’s research team members for COVID-19 acceptance, and leaders of FK UNPATTI. We found an increased percentage of correct answers in the results of the post-test evaluation. At the pre-test, the average percentage of correct answers was 87.4%, and in the post-test the percentage increased to 92.8%. In the pre-test, 89% of participants were categorized as having a high level of knowledge, while in the post-test evaluation, the percentage increased to 93.4%. This webinar could improve participants’ knowledge and therefore could be conducted in the future as part of FK UNPATTI contributions in preventing COVID-19 transmission in Ambon City. ABSTRAK Jumlah kasus dan kematian akibat COVID-19 terus mengalami penurunan seiring meningkatnya cakupan vaksinasi.  Di Indonesia, cakupan vaksinasi COVID-19 sayangnya masih belum memenuhi target nasional, termasuk di wilayah Kota Ambon. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan civitas akademika Universitas Pattimura serta tenaga Kesehatan di RSUD Dr. M Haulussy sebagai RS rujukan utama COVID-19 di Kota Ambon tentang perkembangan dan pentingnya program vaksinasi COVID-19. Kegiatan dilakukan oleh Fakultas Kedokteran Universitas Pattimura (FK UNPATTI) pada 10 Desember 2021 dalam bentuk webinar edukasi. Sebanyak 275 peserta (termasuk mahasiswa, staf pengajar, serta tenaga kesehatan RSUD Dr. M. Haulussy) mengisi secara lengkap kuesioner evaluasi (pre- dan post-test). Narasumbe dalam webinar ini berasal dari Dinas Kesehatan Kota Ambon, tim peneliti studi penerimaan vaksinasi COVID-19 dari FK UNPATTI, serta pimpinan FK UNPATTI. Pengisian kuesioner pre dan post-test menunjukkan peningkatan persentase jawaban benar peseta webinar pada evaluasi post-test. Pada pre-test, rerata persentase jawaban benar peserta adalah 87,4% sedangkan pada post-test meningkat menjadi 92,8%.  Pada evaluasi pre-test, 89% peserta dikategorikan memiliki pengetahuan tinggi, sedangkan pada post-test, persentase ini meningkat menjadi 93,4%. Kegiatan webinar ini diharpakan dapat dilakukan untuk mendukung peningkatan pengetahuan peserta dan sekaligus sebagai kontribusi FK UNPATTI dalam pengendalian transmisi COVID-19 di Kota Ambon.